2017
DOI: 10.1080/10803548.2017.1353321
|View full text |Cite
|
Sign up to set email alerts
|

Influence of type of MVC test on electromyography measures of biceps brachii and triceps brachii

Abstract: Objective. This study aimed to investigate the amplitude and frequency measures of the electromyography (EMG) signal in agonistic and antagonistic muscles (biceps brachii, triceps brachii). Methods. Fifteen males (22.9 ± 2.1 years old) took three isometric maximum voluntary contraction (MVC) tests. Two tests were typical MVC tests for biceps brachii and triceps brachii. The third was a test often used to obtain MVC for forearm muscles (arm and forearm hanging down). The EMG signal was recorded during three iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In addition, the role of the muscle in force exertion also affects the amplitude and frequency of the EMG. Roman- Liu and Bartuzi (2018) have found that when the BB and TB function as antagonists, their frequency measures show lower values than when these muscles work as agonists. When acting as stabilizers, BB shows a much lower amplitude than during agonist with similar spectral measures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the role of the muscle in force exertion also affects the amplitude and frequency of the EMG. Roman- Liu and Bartuzi (2018) have found that when the BB and TB function as antagonists, their frequency measures show lower values than when these muscles work as agonists. When acting as stabilizers, BB shows a much lower amplitude than during agonist with similar spectral measures.…”
Section: Discussionmentioning
confidence: 99%
“…As we consulted with the professor of Physical Education and Sports Teaching (Karamanoğlu Mehmetbey University), he stated that the fall was caused by the distortion of movement. According to the consultant professor, this change appeared to have been caused by the prolongation of the activation period of the muscle as a result of pushing the weight down more slowly as specified in [64, 65].…”
Section: Resultsmentioning
confidence: 99%
“…The list of determined electromyographic parameters included the amplitude of bioelectrical signal from the longissimus muscle, expressed in microvolt. Avoiding a confounding effect associated with measurement conditions, the results were normalized to a reference Maximum Voluntary Contraction (MVC) and expressed in percent [17]. After fixation of the electrodes and preparation of the system, MVC of the longissimus was determined according to the international SENIAM guidelines [16].…”
Section: Methodsmentioning
confidence: 99%